PROBLEMATIKA EKSISTENSI MODAL VENTURA SYARIAH DALAM PERSPEKTIF EKONOMI ISLAM (Studi Pada Perusahaan Permodalan Nasional Madani ventura Syariah Jakarta) - Sulistyowati Sulistyowati (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2020)
The research to be carried out is a field research and a documentary to answer questions chronologically and systematically about the role and problems of the existence of sharia venture capital in improving micro, small and medium enterprises (MSMEs). The research method used in this study is an inductive method. The results of this study explain the role and function of venture capital in improving (MSMEs) as PPU, especially those who are new start-ups starting their business with limited capital and do not have assets to be used as collateral for the financing guarantee according to the characteristics of PMVS in financing without any collateral and It is also very helpful for business partner companies (PPU) that are feasible (worthy of funding) but are not bankable (does not meet banking requirements) that are on the black list of other financial institutions, but have the determination and earnest spirit to continue to develop their business with good prospects. promising. In addition to providing business capital financing assistance, venture capital companies are also involved in mentoring the business development management of business partner companies (PPU). Strategies for developing sharia venture capital that can be carried out include intensive and comprehensive socialization from both practitioners and academics so that public literacy understanding of sharia venture capital companies increases, expansion of venture capital funding for PMVS from various parties, both domestic and foreign, not domestically. only limited to Islamic financial institutions but can synergize with other institutions, for example in collaboration with BPKH (Hajj Financial Management Agency) and foreign loans, namely IDB (Islamic Development Bank), increasing reliable and professional human resources by holding training, workshops , increasing capacity building, and improving the management system of sharia venture capital companies, especially sharia strategic management efforts to realize operational activities that are truly based on sharia principles, and there is an effort to approach networking with government agencies so that with the hope there is government intervention as a policy maker in synergy with the OJK regulator on sharia venture capital companies.